The Effectiveness of Tamarind Turmeric Water on the Dysmenorrhea Pain Scale in Teenage Girl - Nadya Lestari; Tubagus Erwin N; Septi Nura Astuti (Talenta Publisher, 2023)
Dysmenorrhea, or menstrual pain, is one of the most common gynaecological complaints among teenage girls. Menstrual pain is a symptom and not a disease. One herbal remedy that can be consumed by teenage girls to alleviate dysmenorrhea is tamarind turmeric drink. The purpose of this study was to assess the effectiveness of tamarind turmeric water in reducing menstrual pain in teenage girls. This research is quantitative in nature, utilizing a pre-experimental research design with the One Group Pre-Test Post Test approach. Sample calculation results indicate a total of 29 respondents using accidental sampling. Results: Based on statistical tests, a p-value of 0.000 was obtained, which is less than 0.05, indicating the effectiveness of tamarind and turmeric water in reducing dysmenorrhea pain in teenage girls at Integrated Vocational School Waway Karya, East Lampung, in 2023. It is expected that respondents will establish a more regular routine of consuming tamarind turmeric water to reduce pain and maintain healthy eating habits, such as avoiding spicy, oily foods, alcoholic beverages, and maintaining good hygiene practices.